Theory of electrochemistry at miniaturised interfaces between two immiscible electrolyte solutions - Arrigan, Damien; Herzog, G. (Elsevier, 2017)
In this current opinion article on the electrochemistry of micro- and nano-interfaces between two immiscible electrolyte solutions, we present a summary of theoretical descriptions to-date, rather than only of work in the past ca. 2 years. The opinion summarises the current state of art in the theory used to interpret and analyse this form of experimental electrochemistry, specifically addressing only simple ion transfer processes.